CT based three-dimensional measurement of adult orbit in Hospital Universiti Sains Malaysia - Chee Kong, Lee (2015)
Purpose: To correlate the orbital parameters with age, race and gender of the HUSM population for forensic radiology future reference. Materials and methods: In an institutional review board-approved study, the authors obtained 126 samples referred to HUSM Radiology Department for CT scan of the head. Measurement of the orbital parameters is done on reconstructed 3D images using electronic calipers on workstation screen with the supervision of the supervisor, a senior radiologist with more than 30 years of experience in the Head and Neck imaging. Correlation and regression was used to assess the association between the orbital parameters with patient’s age, race and gender. Results: We were able to obtain 126 patients in which 113 were Malays, 13 were non-Malays, 68 were male and 58 were female. There was a significant correlation between the left and right orbital height (regression line 0.877), orbital width (regression line 0.759) and orbital perimeter (regression line 0.850). There was no significant statistical difference with race correlation and the orbital anthropometry. In terms of correlation with gender, independent t-test showed there was significant statistical difference in the left orbital height (mean difference 0.05), right orbital height (mean difference 0.06) and right orbital perimeter (mean difference 0.16). One way ANOVA showed that in terms of age, there was a significant statistical difference between the left orbital width (mean difference 0.16), right orbital width (mean difference 0.15) and left orbital perimeter (mean difference 0.43). Conclusions: This study provided useful baseline anthropometric data that will be of clinical and surgical interest in ophthalmology, oral and maxillofacial surgery in Kelantan. We recommended that anthropologists, clinicians and forensic experts to obtain this data and use them in any way deemed necessary for the quest of research and knowledge.